A Paleoeskimo Occupation on Southern Banks Island, N.W.T. - Arnold, Charles D. (ARCTIC, 1980)
Significant changes occurred within Paleoeskimo cultures during the first millenium B.C. Archaeological remains from the Lagoon site, on Banks Island, N.W.T., provide a new perspective on the nature of those changes and insights into some of the processes involved.